MENGGALI POTENSI SEKTOR PANGAN MELALUI INOVASI PENGOLAHAN NUGGET TEMPE DAUN KELOR PADA UMKM DI KECAMATAN KASIHAN YOGYAKARTA - Citra Nur Syafira; Yeni Yeni; Endah Dewi Purnamasari (LPPM Institut Pendidikan Nusantara Global, 2025)
Training on processing Moringa leaf tempeh nuggets in Kasihan District, Yogjakarta, aims to improve community skills in utilizing local, highly nutritious food ingredients, as well as encouraging innovation in food products with marketable value. This service activity is carried out using a participatory approach, through direct training methods, involving housewives, MSME actors and village youth. The training material includes an introduction to raw materials, processing techniques for Moringa leaf tempeh nuggets, packaging, and product marketing strategies. The results of the training showed a significant increase in the participants' skills, participants were able to produce nugget products that met standards of cleanliness, food safety and creativity in shape. In addition, participants began to market their products independently. This training not only has an impact on improving technical skills, but also contributes to strengthening local food security and opportunities for developing small businesses in the community. It is hoped that these findings can become a model for local food-based community empowerment that can be replicated in other regions.